If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2 + -1a)(5z + -7) = 0 Reorder the terms: (2 + -1a)(-7 + 5z) = 0 Multiply (2 + -1a) * (-7 + 5z) (2(-7 + 5z) + -1a * (-7 + 5z)) = 0 ((-7 * 2 + 5z * 2) + -1a * (-7 + 5z)) = 0 ((-14 + 10z) + -1a * (-7 + 5z)) = 0 (-14 + 10z + (-7 * -1a + 5z * -1a)) = 0 (-14 + 10z + (7a + -5az)) = 0 Reorder the terms: (-14 + 7a + -5az + 10z) = 0 (-14 + 7a + -5az + 10z) = 0 Solving -14 + 7a + -5az + 10z = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 7a + -5az + 14 + 10z = 0 + 14 Reorder the terms: -14 + 14 + 7a + -5az + 10z = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 7a + -5az + 10z = 0 + 14 7a + -5az + 10z = 0 + 14 Combine like terms: 0 + 14 = 14 7a + -5az + 10z = 14 Add '-10z' to each side of the equation. 7a + -5az + 10z + -10z = 14 + -10z Combine like terms: 10z + -10z = 0 7a + -5az + 0 = 14 + -10z 7a + -5az = 14 + -10z Reorder the terms: -14 + 7a + -5az + 10z = 14 + -10z + -14 + 10z Reorder the terms: -14 + 7a + -5az + 10z = 14 + -14 + -10z + 10z Combine like terms: 14 + -14 = 0 -14 + 7a + -5az + 10z = 0 + -10z + 10z -14 + 7a + -5az + 10z = -10z + 10z Combine like terms: -10z + 10z = 0 -14 + 7a + -5az + 10z = 0 The solution to this equation could not be determined.
| x/3-4=x-7 | | -4a+2=4a+82 | | e/-6=4 | | -7x+10=-3x+22 | | (72-x)=180 | | 5[7-5(-2x-9)]=50x+260 | | 6-2z=2z-10 | | (4x+32)=180 | | 20-1/10d=16 | | 5y+140=7x | | 22.27/x=4.16 | | 3x+2x^2-8x+6x^2= | | 22.27*x=4.16 | | x+22=34 | | 15=2x+10 | | x+22=33 | | 22.27*x=22.27 | | -2e^3x+19=3 | | 5y=7x-140 | | -x^2+6x=-1 | | 154/22 | | 11-3h+9=-8 | | 4x+1=2x+29 | | 3x-4=5x+9 | | https://www.mhcitts.com/images/test/53_1_8s.jpg | | 3x-7=6x-2 | | 165x+2771=7721 | | 2x(-5)=6x^2-11x | | 4/5x-3/4y=-10 | | 11+3h+9=-8 | | 10+6x=50 | | x+(x*0.23)=22.27 |